(untitled) (ESMAT Magazine, 2019)
This article deals with the State and Economy interface. having as object the Federal Constitution and the Economic Law. We will investigate the two sides, positive and negative of this systematic relationship. The epistemological cut is drawn from the analysis between constitutional values, such as justice, ethics and humanism, and its overlap with capitalism, as a primordial element to material progress. It is justified to speak of constitutional axiology and capitalism, given the deep social and regional inequalities in the country, as well as the fact that both are essential to human achievement and to sustainable development in Brazil. The problem that emerges is to investigate whether there is a legal analysis of the economy or whether there is a submission of the right to the economy. Hypothetically, the implantation of a humanist capitalism is a development factor. The theoretical framework is based on modern humanist theories, using the deductive method and exhaustive bibliographical research.